Fernand Braudel e a geo-história das civilizações Fernand Braudel and the geo-history of civilizations - Guilherme Ribeiro (História, Ciências, Saúde: Manguinhos, 2011)
Discute a importância da geografia para o estudo das civilizações no livro Grammaire des civilisations, do historiador francês Fernand Braudel, bem como o papel epistemológico do conceito de geo-história em seu pensamento. Parte da hipótese de que a geografia foi crucial para a apreensão da história de longa duração. The article discusses the valuable role of geography in the study of civilizations entitled Grammaire des civilisations (A history of civilizations), by French historian Fernand Braudel. It also focuses on the epistemological role of the concept of geo-history in Braudel's thought. The article's underlying assumption is that geography has been crucial to comprehending history over large spans of time.